PTSD and the klotho longevity gene: Evaluation of longitudinal effects on inflammation via DNA methylation. (July 2020) - Wolf, Erika J.; Logue, Mark W.; Zhao, Xiang; Daskalakis, Nikolaos P.; Morrison, Filomene G.; Escarfulleri, Shaline; Stone, Annjanette; Schichman, Steven A.; McGlinchey, Regina E.; Milberg, William P.; Chen, Cidi; Abraham, Carmela R.; et al.
Highlights: Klotho (KL) confers risk for accelerated aging, especially given psychiatric stress. The role of KL DNA methylation in this is unknown. KL variant rs9527025 showed strong associations with methylation at cg00129557. rs9527025 X PTSD predicted inflammation over time via methylation at cg00129557. KL methylation may be a mechanism linking genotype to accelerated aging. Abstract: Background: Longevity gene klotho ( KL ) is associated with age-related phenotypes including lifespan, cardiometabolic disorders, cognition, and brain morphology, in part, by conferring protection against inflammation. We hypothesized that the KL /inflammation association might be altered in the presence of psychiatric stress and operate via epigenetic pathways. We examined KL polymorphisms, and their interaction with posttraumatic stress disorder (PTSD) symptoms, in association with KL DNA methylation in blood. We further examined KL DNA methylation as a predictor of longitudinal changes in a peripheral biomarker of inflammation (C-reactive protein; CRP). Methods: The sample comprised 309 white non-Hispanic military veterans (93.5 % male; mean age: 32 years, range: 19–65; 30 % PTSD per structured diagnostic interview); 111 were reassessed approximately two years later. Results: Analyses revealed a methylation quantitative trait locus at rs9527025 (C370S, previously implicated in numerous studies of aging) in association with a Cytosine-phosphate-Guanine site (cg00129557; B = −.65, p = 1.29 X 10 −20 ), located within a DNase hypersensitivity site in the body of KL . There was also a rs9527025 x PTSD severity interaction (B = .004, p = .035) on methylation at this locus such that the minor allele was associated with reduced cg00129557 methylation in individuals with few or no PTSD symptoms while this effect was attenuated in those with elevated levels of PTSD. Path models revealed that methylation at cg00129557 was inversely associated with CRP over time (B = −.14, p = .005), controlling for baseline CRP. There was also an indirect effect of rs9527025 X PTSD on subsequent CRP via cg00129557 methylation (indirect B = −.002, p = .033). Conclusions: Results contribute to our understanding of the epigenetic correlates of inflammation in PTSD and suggest that KL methylation may be a mechanism by which KL genotype confers risk vs. resilience to accelerated aging in those experiencing traumatic stress.